Familial Hemophagocytic Lymphohistiocytosis: When Rare Diseases Shed Light on Immune System Functioning - Sieni, Elena; Cetica, Valentina; Hackmann, Yvonne; Coniglio, Maria Luisa; Da Ros, Martina; Ciambotti, Benedetta; Pende, Daniela; Griffiths, Gillian; Aricò, Maurizio (Frontiers in Immunology, 2014)
The human immune system depends on the activity of cytotoxic T lymphocytes, Natural Killer cells, and NKT cells in order to fight off a viral infection. Understanding the molecular mechanisms during this process and the role of individual proteins was greatly improved by the study of Familial Hemophagocytic Lymphohistiocytosis (FHL). Since 1999, genetic sequencing is the gold standard to classify patients into different subgroups of FHL. The diagnosis, once based on a clinical constellation of abnormalities, is now strongly supported by the results of a functional flow-cytometry screening, which directs the genetic study. A few additional congenital immune deficiencies can also cause a resembling or even identical clinical picture to FHL. As in many other rare human disorders, the collection and analysis of a relatively large number of cases in registries is crucial to draw a complete picture of the disease. The conduction of prospective therapeutic trials allows investigators to increase the awareness of the disease and to speed up the diagnostic process, but also provides important functional and genetic confirmations. Children with confirmed diagnosis may undergo hematopoietic stem cell transplantation, which is the only cure known to date. Moreover, detailed characterization of these rare patients helped to understand the function of individual proteins within the exocytic machinery of CTL, NK and NKT cells. Moreover, identification of these genotypes also provides valuable information on variant phenotypes, other than FHL, associated with biallelic and monoallelic mutations in the FHL-related genes. In this review we describe how detailed characterization of patients with genetic HLH has resulted in improvement in knowledge regarding contribution of individual proteins to the functional machinery of cytotoxic T-cells and NK cells. The review also details how identification of these genotypes has provided valuable information on variant phenotypes.